2018
DOI: 10.3889/oamjms.2018.196
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variations of Pancreaticobiliary Union

Abstract: AIM:This study was designated to evaluate the frequency of anatomic variations of the pancreaticobiliary union.MATERIALS AND METHODS:Our research was observational, comparative and analytical. The investigation was conducted from January 2016-May 2017. This study included 63 patients from Clinic of Gastroenterology and Hepatology – Prishtina, assessed pancreaticobiliary union with Magnetic Resonance cholangiopancreatography.RESULTS:Union of the common bile duct and the major pancreas was biliary-pancreatic typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…[9][10][11][12][13] In our study we have used the classification based on other studies. 1,3 In another study done in 694 cases showed the average length of the common channel was 7.9 mm with 241 (34.70% ) anomalous unions which were 84 (12.1%) PB type, 85 (12.2%) BP type and 72 (10.4%) separate type. 2 In our study, the average length of the common channel was 9.53±3.24 mm which was similar to this study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…[9][10][11][12][13] In our study we have used the classification based on other studies. 1,3 In another study done in 694 cases showed the average length of the common channel was 7.9 mm with 241 (34.70% ) anomalous unions which were 84 (12.1%) PB type, 85 (12.2%) BP type and 72 (10.4%) separate type. 2 In our study, the average length of the common channel was 9.53±3.24 mm which was similar to this study.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, we have used the classification given by two different studies. 1,3 The 3D SPACE images were reformatted with Maximum Intensity Projection (MIP). These images were then visually analyzed to determine the anatomic variation of the pancreaticobiliary union.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermittent mechanical obstruction, such as Sphincter of Oddi dysfunction, where the duodenal sphincter fails to relax normally, along with anatomic variations in the union of the PD and common bile duct (CBD), are rare causes of recurrent AP. 7 Up to 10% of AP is due to infection, e.g. mumps 8 or salmonella.…”
Section: Introductionmentioning
confidence: 99%